Study on the predictive role of bile acid and lymphocyte count in the prognosis of patients with traumatic brain injury: a retrospective analysis - Xu, Jie; Song, Yinghua; Chen, Xiancheng; Chen, Ming; Zhao, Yun; Li, Zhi; Li, Songyang; Zhang, Liang; Yu, Wenkui (Frontiers in Neurology, 2025)
ObjectivesIn patients with traumatic brain injury (TBI), primary traumatic brain injury is often accompanied by gastrointestinal immune dysfunction. Disruption of gut microbiota, abnormal metabolic products of gut microbiota, and immune dysfunction in the body after traumatic brain injury may lead to secondary traumatic brain injury. Bile acids are common metabolites of the gut microbiota in clinical practice, and lymphocyte count is one of the indicators reflecting the clinical immune function of patients. We conducted a retrospective analysis to investigate the value of factors such as bile acids and lymphocyte counts in predicting 30 day mortality in patients with traumatic brain injury.MethodsThis study included 165 patients with TBI and 131 healthy individuals who underwent physical examinations during the same period as the control. The results revealed that compared to the control group, patients with TBI had significantly lower levels of bile acids and lymphocyte counts. Regression analysis reported a correlation between GCS score, bile acid level, lymphocyte count, and 30-day mortality rate in TBI patients. Patients with lower GCS, lower bile acids, and lower lymphocyte counts after TBI have a significantly higher mortality rate during hospitalization.ResultsCompared with healthy individuals undergoing physical examination, the serum bile acid levels of TBI patients were significantly reduced (7.20 ± 2.83 vs. 3.45 ± 1.97 μ mol/L, p < 0.001). Compared with healthy individuals undergoing physical examination, the lymphocyte count of TBI patients (4.61 ± 1.72 vs. 1.49 ± 0.88 × 109/L, p < 0.001) was significantly reduced. Multiple logistic regression analysis of risk factors for 30 day mortality in TBI patients revealed a correlation between bile acids and mortality (OR 0.748 [0.566–0.988]; p = 0.041), as well as a positive correlation between lymphopenia and 30 day mortality (OR 0.494 [0.300–0.815]; p = 0.006). For TBI patients, bile acid levels, lymphocyte counts, and GCS scores are equally sensitive and specific for predicting 30 day mortality. AUC, Area under the curve. GCS (AUC = 0.7008, p = 0.0004), BA (AUC = 0.7274, p < 0.0001), LYC (AUC = 0.6678, p = 0.0029).ConclusionThis study provides preliminary clinical evidence for the correlation between bile acid levels, immune function, and mortality in TBI patients. Further research is needed to verify the mechanism of their correlation and provide a theoretical basis for intervening in secondary brain injury after TBI and reducing clinical mortality.